If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2n + -4 = -24 Reorder the terms: -4 + -2n = -24 Solving -4 + -2n = -24 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -2n = -24 + 4 Combine like terms: -4 + 4 = 0 0 + -2n = -24 + 4 -2n = -24 + 4 Combine like terms: -24 + 4 = -20 -2n = -20 Divide each side by '-2'. n = 10 Simplifying n = 10
| (8+7)+(9-2)=18 | | 6r+9=6(r+1)+3 | | v/-28=-31 | | 4x-4=4+X+3 | | 12+x=15-12x | | 10r+5=35 | | c-13.7=-10.7 | | 2(x-5)+3x=4x-3 | | -16=m/3-20 | | y+82=591 | | 3r-28=8(1+4r)+7r | | 30z=450 | | 2=m/4-1 | | Log(4)8x+log(4)4=3 | | -31=c/-16 | | 6=-2(3p+3) | | 2y+13=2y+19 | | 350x+xy-200=0 | | c+-102=277 | | -4x-4=32 | | -p-4=2 | | -0.26=log(x) | | 11-3f=2 | | 3.8/4 | | -8x^2+3-10x=0 | | 5(-4x+7)=175 | | m+-77=-50 | | -p+2=-3 | | -3c=-81 | | -75=v-83 | | 8x-4=2x+8+x | | p+20=32 |